The Effect of Environment and Self-Regulated Learning on Learning Interest at Social Geography Courses: A Quantitative Approach - Alamsyah, Risky; Amin, Saiful (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2026)
Learning interest is essential for student engagement and learning quality in higher education, particularly in Social Geography, where students must connect theoretical concepts with socio-spatial realities. This study aimed to analyze the partial and simultaneous effects of the learning environment and self-regulated learning on students’ learning interest. A quantitative explanatory design was used involving 113 students from the 2024 cohort of the Social Science Education Study Program at Universitas Islam Negeri Maulana Malik Ibrahim Malang, selected from 158 students through simple random sampling using Slovin’s formula. Data were collected using a closed-ended questionnaire and analyzed through multiple linear regression with SPSS version 23. The results showed that the learning environment and self-regulated learning had positive and significant effects on learning interest, both partially and simultaneously. Both variables explained 75.0% of the variance, with self-regulated learning as the stronger predictor. These findings support SDG 4 by emphasizing supportive learning environments and lifelong learning capacity